The pandemic evolution and its impact on the Italian school - Bianchi Matè, Giulia; Toscano, Emanuele (Community Notebook. People, Education and Welfare in the Society 5.0, 2023)
The essay examines the pandemic impact on educational and school Italian system expressing the requirement to realize a new approach in order to exceed distance/presence combination. This approach has allowed the input towards an interconnected and multimedia knowledge that has enhanced the narration and the relationship with the territory/environment. The pandemic had numerous implications that have been investigated through the analyses of psychologists, sociologists, philosophers, educators.